(untitled) (International Journal of Innovative Technologies in Economy, 2019)
Recent structural changes in the economy of the Nagorno-Karabakh Republic have had a significant impact on the entire public relations system, obliging to review the mechanisms for making economic decisions as primary ones. The formation of NKR coincided with the collapse of the USSR and with the radical changes in the system of economic relations that led to this. Since its formation, local authorities have adopted a strategy for the development of the construction sector by stimulating investment, which intends the creation of a favorable investment environment and the development of an appropriate infrastructure. Despite the fact that NKR construction sector has great potential for attracting investments, the level of foreign investors’ activity in this area is quite low. The main reason is probably a high risk level, which is determined by such factors as political instability in the region, the geographical location of NKR, its economic isolation, an incomplete legal framework, and the underdevelopment of financial and market infrastructures. As a result, many investment projects, including cost-effective and efficient ones, are not implemented. Uncertainty associated with the possibility of adverse situations and consequences during the implementation of the project is characterized by the concept of “risk”. The effectiveness of the risk management organization is largely determined by the classification of risk. Depending on the main cause of the risk (basic or natural risk), the classification of risks associated with the implementation of investment construction projects provides a favorable basis for a clear and reasonable risk assessment, which is one of the crucial factors in the effectiveness of the risk management process.